2021
DOI: 10.1002/net.22085
|View full text |Cite
|
Sign up to set email alerts
|

Uniformly optimally reliable graphs: A survey

Abstract: Which is the most reliable graph with n nodes and m edges? This celebrated problem has several aspects, according to the notion of optimality (in a local or uniform sense), failure type (either nodes or edges), or reliability model (all‐terminal connectedness, two‐terminal or multiterminal setting). This article presents a chronological survey of the multiple proposals to address the problem, together with recent trends and enigmatic conjectures posed decades ago that promote further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Here, collective functionality assures redundancy, while independence maintains modularity. We need more comprehensive complex network analyses quantifying these benefits (e.g., Romero, 2021), to guide topological design for DWSs that are affordable and robust under both normal and contingency conditions.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Here, collective functionality assures redundancy, while independence maintains modularity. We need more comprehensive complex network analyses quantifying these benefits (e.g., Romero, 2021), to guide topological design for DWSs that are affordable and robust under both normal and contingency conditions.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The study of similar notions of optimal graphs has occupied a number of researchers in other areas of reliability (such as all-terminal and two-terminal), where only partial results are known about the existence or non-existence of such graphs. The reader can consult a recent survey of uniformly optimally reliable graphs in [8] as well as practical guidelines in [4]. A study of the most-reliable multigraphs can be found in [2,6,7].…”
Section: Optimal Graphsmentioning
confidence: 99%
“…The topic of networks, and more specifically the reliability of networks, has been extensively studied. (See References [4,9,10] for recent survey papers on the topic.) These networks are modeled using graphs where the vertices of the graph represent the nodes of the network, and the edges of the graph represent node connections.…”
Section: Introductionmentioning
confidence: 99%